Motor unit dysregulation following 15 days of unilateral lower limb immobilisation. (5th October 2022) - Inns, Thomas B.; Bass, Joseph J.; Hardy, Edward J.O.; Wilkinson, Daniel J.; Stashuk, Daniel W.; Atherton, Philip J.; Phillips, Bethan E.; Piasecki, Mathew
Abstract : Abstract: Disuse atrophy, caused by situations of unloading such as limb immobilisation, causes a rapid yet diverging reduction in skeletal muscle function when compared to muscle mass. While mechanistic insight into the loss of mass is well studied, deterioration of muscle function with a focus towards the neural input to muscle remains underexplored. This study aimed to determine the role of motor unit adaptation in disuse‐induced neuromuscular deficits. Ten young, healthy male volunteers underwent 15 days of unilateral lower limb immobilisation with intramuscular electromyography (iEMG) bilaterally recorded from the vastus lateralis (VL) during knee extensor contractions normalised to maximal voluntary contraction (MVC), pre and post disuse. Muscle cross‐sectional area was determined by ultrasound. Individual MUs were sampled and analysed for changes in motor unit (MU) discharge and MU potential (MUP) characteristics. VL CSA was reduced by approximately 15% which was exceeded by a two‐fold decrease of 31% in muscle strength in the immobilised limb, with no change in either parameter in the non‐immobilised limb. Parameters of MUP size were reduced by 11% to 24% with immobilisation, while neuromuscular junction (NMJ) transmission instability remained unchanged, and MU firing rate decreased by 8% to 11% at several contraction levels. All adaptations were observed in the immobilised limb only. These findings highlight impaired neural input following immobilisation reflected by suppressed MU firing rate which may underpin the disproportionate reductions of strength relative to muscle size. Key points: Muscle mass and function decline rapidly in situations of disuse such as bed rest and limb immobilisation. The reduction in muscle function commonly exceeds that of muscle mass, which may be associated with the dysregulation of neural input to muscle. We have used intramuscular electromyography to sample individual motor unit and near fibre potentials from the vastus lateralis following 15 days of unilateral limb immobilisation. Following disuse, the disproportionate loss of muscle strength when compared to size coincided with suppressed motor unit firing rate. These motor unit adaptations were observed at multiple contraction levels and in the immobilised limb only. Our findings demonstrate neural dysregulation as a key component of functional loss following muscle disuse in humans. Abstract : Abstract figure legend Ten healthy young males underwent 15 days of unilateral lower limb immobilisation with an irremovable leg brace. Muscle size, strength, and neuromuscular characteristics were measured bilaterally. Muscle strength reduced to a greater extent than muscle size in the immobilised leg while remaining unaltered in the non‐immobilised leg. Motor unit firing rate, measured bilaterally using intramuscular electromyography, was also reduced in the immobilised leg only. This occurred at contraction intensities both relative to follow‐up muscle strength and muscle strength normalised to pre‐immobilisation. These findings suggest that neural dysregulation contributes to the loss of muscle strength observed in situations of disuse atrophy in humans.